Epilepsy Smart School: Part Of Anti Stigma Campaign - Husna, Machlusil; Damayanti, Ria; Harbiyanti, Novita Titis; Rahma, Annisa; Gumelar, Enggar; Ibrahim, Ananto Suarbhakti; Muhammad, Galang Mahasin; Kurniasari, Dyah Ayu (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2025)
Epilepsy is a neurological condition that is still frequently associated with stigma and misconceptions, particularly in school settings, which can lead to discrimination, social exclusion, and inappropriate seizure management. As part of a community service, The Epilepsy Smart School program was implemented from May to December 2025 in Malang, Indonesia, aiming to improve knowledge, reduce stigma, and promote inclusion for students with epilepsy through interactive education and seizure first-aid simulations. Evaluation was conducted using a pre–post assessment design involving 30 participants (students and teachers) selected through convenience sampling. The results showed a significant increase in knowledge scores from 81.0 to 98.6, reflecting a better understanding of epilepsy and appropriate seizure management. In addition, stigma was reduced, as indicated by increased social acceptance, empathy, and willingness to interact with and support inclusive education without segregation. Although there was a decrease in post-test participation and no long-term evaluation was conducted, the program proved effective in improving both cognitive and social attitude aspects. These findings suggest that participatory school-based health education has the potential to create a more inclusive, supportive, and stigma-free environment for individuals with epilepsy.